The parent company puzzle: when is the whole worth less than one of the parts? - Cornell, Bradford; Liu, Qaio (Journal of Corporate Finance, 2001)
This paper examines seven instances in which the market value of a parent company was less than the market value of its publicly traded subsidiary. Efforts are made to explain this “parent company puzzle” in terms of taxes, agency costs, liquidity effects and noise trader risk. None of them work. The only explanation consistent with the evidence is a mispricing of the subsidiary shares associated with noise trader demand and impediments to arbitrage. As further evidence in support of this view, five corporate control transactions, all designed to exploit the apparent mispricing, were initiated while this research was in progress.